2019
DOI: 10.1002/lsm.23159
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Blue Light Inactivation of Microbial Isolates in Biofilms

Abstract: Background and Objectives Biofilms cause more than 80% of infections in humans, including more than 90% of all chronic wound infections and are extremely resistant to antimicrobials and the immune system. The situation is exacerbated by the fast spreading of antimicrobial resistance, which has become one of the biggest threats to current public health. There is consequently a critical need for the development of alternative therapeutics. Antimicrobial blue light (aBL) is a light‐based approach that exhibits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 39 publications
1
25
0
1
Order By: Relevance
“…Good examples of these methods include nanoparticles, sonication, irradiation (ultraviolet, visible, or infrared light), or biomaterials. Indeed, blue light, for example, was effective against biofilms formed by A. baumannii , P. aeruginosa , and N. gonorrhoeae although less so against biofilms of E. coli and E. faecalis [ 311 ]. In vivo studies in mouse burns showed that blue-light exposure could drastically reduce bacterial load and effectively protect mice from lethal infection with P. aeruginosa [ 312 ].…”
Section: Control Of Biofilm Infectionsmentioning
confidence: 99%
“…Good examples of these methods include nanoparticles, sonication, irradiation (ultraviolet, visible, or infrared light), or biomaterials. Indeed, blue light, for example, was effective against biofilms formed by A. baumannii , P. aeruginosa , and N. gonorrhoeae although less so against biofilms of E. coli and E. faecalis [ 311 ]. In vivo studies in mouse burns showed that blue-light exposure could drastically reduce bacterial load and effectively protect mice from lethal infection with P. aeruginosa [ 312 ].…”
Section: Control Of Biofilm Infectionsmentioning
confidence: 99%
“…For example, blue light (405 nm; 108–206 J/cm 2 ) significantly inactivated monomicrobial biofilms of drug-resistant A. baumannii , P. aeruginosa and Neisseria gonorrhoeae (4–8 log CFU/mL; p < 0.01 or p < 0.0001), whereas the same blue light treatment did not significantly affect the biofilms of E. coli , E. faecalis and Proteus mirabilis . Further, blue light (405 nm; 216 J/cm 2 ) significantly reduced ( p < 0.01) the number of MRSA in biofilms grown for 24 h, but not in biofilms grown for 48 h [ 250 ].…”
Section: Blue Light Versus Antimicrobial Resistance and Consequencmentioning
confidence: 99%
“…Photobiomodulation using blue light has been largely discussed as an alternative antimicrobial therapy. It shows positive results on in vitro experiments and demonstrates advantages as a treatment when compared with photodynamic therapy and ultraviolet light (Guffey and Wilborn, 2006;Enwemeka et al, 2008Enwemeka et al, , 2009Chui et al, 2012;De Lucca et al, 2012;Bumah et al, 2013Bumah et al, , 2015Dai et al, 2013;Kim et al, 2013;Pileggi et al, 2013;Sousa et al, 2015;Masson-Meyers et al, 2015;Rosa et al, 2016;Ferrer-Espada et al, 2019;Meurer et al, 2019;Rupel et al, 2019;Schmid et al, 2019). Nevertheless, the great variety of experimental protocols using blue light on bacterial inhibition creates difficulty to identify ideal light emission parameters to be adopted with confidence.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus (S. aureus) is a Gram-positive aerobic bacterium, which presents a highly evolved capacity of developing resistance to antimicrobial drugs. Additionally, it is an important etiological agent in skin wound contaminations, often evolving to generalized infections (Enwemeka et al, 2009;Bumah et al, 2013Bumah et al, , 2015Sousa et al, 2015;Freitas et al, 2018;Ferrer-Espada et al, 2019;Rupel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation